(untitled) (Journal of actual problems of jurisprudence, 2018)
The author of this article analyzes the new criminal-political development of the Republic through the prism of the main provisions of the Strategy “Kazakhstan-2050: New political course of the established state”, which reveals the problem of the adoption of the new criminal procedure code in accordance with the Constitution and the norms of international agreements; according to the concept of the draft Criminal procedure code of Kazakhstan, one of the main directions of improvement of the criminal procedural law Concept of legal policy defined simplifying and improving the efficiency of the criminal process, including the simplified pre-trial proceedings. Key words: criminal proceedings, the bodies of pretrial proceedings, plea bargain, institute a criminal case, the simplified production.